Chinese Foreign Investment in Wine Production: A Comparative Study of the Bordeaux Region in France and Western Australia - Curran, L.; Thorpe, Michael (2016)
© 2017 L. Curran and M. Thorpe. All rights reserved. This chapter explores the extent and nature of outward Foreign Direct Investment (OFDI) by Chinese companies in the wine sectors in the Bordeaux region of France and in Western Australia. Primary field research was undertaken along with analysis of secondary trade data. Results indicate that overall, the level of Chinese OFDI is relatively low. The motivations of investors in both wine regions were identified as the following: to exploit growing domestic wine markets; to achieve reliability and security of wine supply and to leverage the prestige that tends to be associated with this industry globally. In Bordeaux the 'appellation' was a clear motivation, as were the vineyards' historic buildings. In Australia, cementing existing business relationships, as well as access to Australian residency were seen to be strong drivers of investment. Recently, both trade to China and new investment from China have fallen in the industry, due, in part, to the impact of an anticorruption drive by the Chinese government. Some managerial implications for the industry are highlighted and directions for future research identified.